Memberdayakan Masyarakat dengan Ketrampilan Pembuatan Pelicin dan Pewangi Pakaian Untuk Meningkatkan Pendapatan di Kelurahan Purwoyoso Kota Semarang - Nurhidayati Nurhidayati; Rahoyo Rahoyo; Nining Hidayah (Journal of Community Service and Engagement, 2022)
The purpose of this community service activity is to help increase income for women in the Purwoyoso village, because the COVID pandemic has reduced income due to a reduction in employees and a reduction in working hours. The method used in this community service activity is to provide direct training with tutorials in the field by teaching how to make clothes lubricants and deodorizers. The results of the service are expected that mothers have skills in making clothes lubricants and fragrances. Having skills in making lubricants and fragrances, mothers can produce which can later be used alone or sold so that additional income can be obtain.